Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Konsumen Pada Industri UKM Olahan Ikan Jaya Utama II Mayangan Probolinggo - Dedi Joko Hermawan (Fakultas Ekonomi Universitas Panca Marga, 2019)
In rise, the current business competition led consumers to be more selective about the products to purchase. This because of many products offered by the manufacturer with a variety of brands, design and the other values in order to create good perception minds of consumers. Product quality is the ability of a product to perform is the function. The brand is a name, symbol, design or combination four of them. Product design is the totality of features that affect the appearance of a specific product according to an implied customer. Purchasing decision is the process of formulating alternatives to settled make a purchase. This research aims to know the influence of both simultaneously and partial from the product quality, brand, design and to the purchasing decision. Design research using surveys, and research methods used associative methods Using Likert scale research Instrument, and analysis techniques using multiple linear regression analysis, considering the model constitutes a number of causal relationships between latent variables. The results showed that the quality of products, band, and designs significantly influence consumer purchasing decisions both simultaneously and partially. Keyword: product quality, band, design, purchase decisions.